Postcolonial Aesthetic Concerns in the Selected Short Fiction of James Joyce’s Dubliners - Huma Ahmed; Rasib Mahmood (Journal of Management Practices, Humanities and Social Sciences, 2024)
In contemporary postcolonial literary theory, few critics (Elleke Boehmer and Bill Ashcroft) have traced an academic gap that shows the need to evaluate postcolonial fiction's aesthetic concerns. The dominance of political concerns hardly leaves room to accept the argument of the simultaneous presence of politics and aesthetics in postcolonial literature. It is observed that the same academic gap can be found in literary research conducted on James Joyce's fiction, where political concerns are highlighted, and aesthetic traits of the literature are neglected. Boehmer argues that postcolonial writing, like any other type, is concerned with aesthetics, structure, reception, and perception. This essay aims to analyze James Joyce's selected short fiction to analyze the aesthetic concerns of postcolonial discourse. Utilizing Boehmer's theoretical stance, postcolonial aesthetics can be located in the writing structure and the act of reading, receiving, and perceiving the text that formulates a unique type of postcolonial poetics. In this way, she gives parallel importance to the author and the reader in determining the aesthetic dimensions of postcolonial fiction. The essay argues that Joyce's writing style/structure allows the aesthetic traits of the text to dominate and subtly neutralize the political overtones of the text. Moreover, the structure of his postcolonial writing influences the reader's reception and perception. His authorship gives birth to postcolonial poetics uniquely different from the simplistic view of postcolonial literature.